The Regulatory Effects of Lateral Hypothalamus Area GABAB Receptor on Gastric Ischemia-Reperfusion Injury in Rats - Gao, Lin; Zhao, Huiru; Zhu, Tao; Liu, Yeliu; Hu, Li; Liu, Zhenguo; Huang, Hai; Chen, Fuxue; Deng, Zhenxu; Chu, Dechang; Du, Dongshu (Frontiers in Physiology, 2017)
Gastric ischemia-reperfusion (GI-R) injury progression is largely associated with excessive activation of the greater splanchnic nerve (GSN). This study aims to investigate the protective effects of GABAB receptor (GABABR) in the lateral hypothalamic area (LHA) on GI-R injury. A model of GI-R injury was established by clamping the celiac artery for 30 min and then reperfusion for 1 h. The coordinate of FN and LHA was identified in Stereotaxic Coordinates and then the L-Glu was microinjected into FN, GABAB receptor agonist baclofen or GABAB receptor antagonist CGP35348 was microinjected into the LHA, finally the GI-R model was prepared. The expression of GABABR, P-GABABR, NOX2, NOX4 and SOD in the LHA was detected by western blot, PCR and RT-PCR. The expression of IL-1β, NOX2 and NXO4 in gastric mucosa was detected by western blot. We found that microinjection of L-Glu into the FN or GABAB receptor agonist (baclofen) into the LHA attenuated GI-R injury. Pretreatment with GABAB receptor antagonist CGP35348 reversed the protective effects of FN stimulation or baclofen into the LHA. Microinjection of baclofen into the LHA obviously reduced the expression of inflammatory factor IL-1β, NOX2 and NOX4 in the gastric mucosa. Conclusion The protective effects of microinjection of GABABR agonist into LHA on GI-R injury in rats could be mediated by up-regulating the production of GABA, GABABR and down-regulating P-GABABR in the LHA.